Buffer‐free therapeutic antibody preparations provide a viable alternative to conventionally buffered solutions: From protein buffer capacity prediction to bioprocess applications. Issue 4 (April 2015) - Bahrenburg, Sven; Karow, Anne R.; Garidel, Patrick
Abstract Protein therapeutics, including monoclonal antibodies (mAbs), have significant buffering capacity, particularly at concentrations >50 mg/mL. This report addresses pH‐related issues critical to adoption of self‐buffered monoclonal antibody formulations. We evaluated solution conditions with protein concentrations ranging from 50 to 250 mg/mL. Samples were both buffer‐free and conventionally buffered with citrate. Samples were non‐isotonic or adjusted for isotonicity with NaCl or trehalose. Studies included accelerated temperature stability tests, shaking stability studies, and pH changes in infusion media as protein concentrate is added. We present averaged buffering slopes of capacity that can be applied to any mAb and present a general method for calculating buffering capacity of buffer‐free, highly concentrated antibody liquid formulations. In temperature stability tests, neither buffer‐free nor conventionally buffered solution conditions showed significant pH changes. Conventionally buffered solutions showed significantly higher opalescence than buffer‐free ones. In general, buffer‐free solution conditions showed less aggregation than conventionally buffered solutions. Shaking stability tests showed no differences between buffer‐free and conventionally buffered solutions. "In‐use" preparation experiments showed that pH in infusion bag medium can rapidly approximate that of self‐buffered protein concentrate as concentrate is added. In summary, the buffer capacity of proteins can be predicted and buffer‐free therapeutic antibody preparations provide a viable alternative to conventionally buffered solutions.